COVID-19-induced disruptions of school feeding services exacerbate food insecurity in Nigeria - Abay, Kibrom A.; Amare, Mulubrhan; Tiberti, Luca; Andam, Kwaw S. (American Society for Nutrition, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic and associated lockdown measures have disrupted educational and nutrition services globally. Understanding the overall and differential impacts of disruption of nutritional (school feeding) services is critical for designing effective post-COVID-19 recovery policies. Objectives: The aim of this study was to examine the impact of COVID-19-induced disruption of school feeding services on household food security in Nigeria. Methods: We combined household-level, pre-COVID-19 in-person survey data with postpandemic phone survey data, along with local government area (LGA)–level information on access to school feeding services. We used a difference-in-difference approach and examined temporal trends in the food security of households with and without access to school feeding services. Of the sampled households, 83% live in LGAs with school feeding services. Results: Households experienced an increase in food insecurity in the post-COVID-19 survey round. The share of households skipping a meal increased by 47 percentage points (95% CI: 44–50 percentage points). COVID-19-induced disruptions of school feeding services increased households' experiences of food insecurity, increasing the probability of skipping a meal by 9 percentage points (95% CI: 3–17 percentage points) and the likelihood of going without eating for a whole day by 3 percentage points (95% CI: 2–11 percentage points). Disruption of school feeding services is associated with a 0.2 SD (95% CI: 0.04–0.41 SD) increase in the food insecurity index. Households residing in states experiencing strict lockdown measures reported further deterioration in food insecurity. Single mothers and poorer households experienced relatively larger deteriorations in food security due to disruption of school feeding services. Conclusions: Our findings show that COVID-19-induced disruptions in educational and nutritional services have exacerbated households’ food insecurity in Nigeria. These findings can inform the designs of immediate and medium-term responses, including the designs of social protection policies and alternative programs to substitute nutritional services affected by the pandemic.